AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN KEUANGAN NEGARA OLEH PEMERINTAHAN DESA SEBAGAI BENTUK TANGGUNG JAWAB PEMERINTAH - Mannan, Faidhul; Dairani, Dairani; Bari , Fathol (Fakultas Ilmu Sosial dan Humaniora, 2023)
In the 1945 Constitution of Indonesia, the government of the Republic of Indonesia acknowledges the existence of villages, customary rights, and commits to respecting diversity while providing constitutional protection to all village communities. Village governments are entrusted with the responsibility of managing village finances in accordance with the provisions set forth in Law Nomor 6 of 2014 concerning Villages. This responsibility encompasses financial management, assets, and village income, all aimed at improving the quality of life for the village population. Despite the potential for issues such as fraud and corruption committed by village officials or village governments, this research primarily focuses on the position of village finances within the framework of national financial oversight and the implementation of supervision over village financial management in accordance with village financial regulations in Indonesia. To establish the position of village finances as an integral part of national finances, there is a need for new legal provisions and incentives that unequivocally state that village finances are indeed a component of national finances. The implementation of oversight over national financial management is governed by Regulation of the Minister of Home Affairs Nomor 73 of 2020, whicinvolves various stages including planning, execution, reporting, and follow-up supervision.